Effectiveness and Safety of Clonazepam, Pregabalin, and Alpha Lipoic Acid for the Treatment of Burning Mouth Syndrome - ÇİNAR, SALİH LEVENT; KARTAL, DEMET; Pergel, TAHA; PERGEL, TAHA; BORLU, MURAT (My University, 2018)
Objective: Burning mouth syndrome is characterized by pain in the oral mucosa with no visible organic pathology. Few treatment options are available; however, none of them are gold-standard. Here we evaluated the effectiveness and safety of Clonazepam. pregabalin. and alpha lipoic acid for treating burning mouth syndrome.